Imaging of the Bursae - Hirji, Zameer; Hunjun, Jaspal S; Choudur, Hema N
When assessing joints with various imaging modalities, it is important to focus on the extraarticular soft tissues that may clinically mimic joint pathology. One such extraarticular structure is the bursa. Bursitis can clinically be misdiagnosed as joint-, tendon- or muscle-related pain. Pathological processes are often a result of inflammation that is secondary to excessive local friction, infection, arthritides or direct trauma. It is therefore important to understand the anatomy and pathology of the common bursae in the appendicular skeleton. The purpose of this pictorial essay is to characterize the clinically relevant bursae in the appendicular skeleton using diagrams and corresponding multimodality images, focusing on normal anatomy and common pathological processes that affect them. The aim is to familiarize radiologists with the radiological features of bursitis.